Two Decades of Family Change: The Shifting Economic Foundations of Marriage - Sweeney, Megan M. (American Sociological Review, 2002)
Has the relationship between economic prospects and marriage formation in the United States changed in recent decades? To answer this question, a discrete-time event-history analysis was conducted using data from multiple cohorts of the National Longitudinal Surveys of Labor Market Experience. Among women, results indicate growth in the importance of earnings for marriage formation between the early baby-boom cohort (born between 1950 and 1954) and late baby-boom cohort (born between 1961 and 1965). Evidence of cohort change in the relationship between men's economic prospects and marriage, however, is limited. Despite important racial differences in the economic and attitudinal context of marriage, key results are generally similar for whites and for African Americans. Taken together, these findings imply that men and women are growing to resemble one another with respect to the relationship between economic prospects and marriage, although this convergence is driven primarily by changing patterns of marriage among women. These results are largely supportive of Oppenheimer's career-entry theory of marriage and suggest that Becker's specialization and trading model of marriage may be outdated.